Competition in the British Electricity Spot Market - Green, Richard J.; Newbery, David M. (Journal of Political Economy, 1992)
Most of the British electricity supply industry has been privatized. Two dominant generators supply bulk electricity to an unregulated "pool." They submit a supply schedule of prices for generation and receive the market-clearing price, which varies with demand. Despite claims that this should be highly competitive, the authors show that the Nash equilibrium in supply schedules implies a high markup on marginal cost and substantial deadweight losses. Further simulations, to show the effect of entry by 1994, produce somewhat lower prices at the cost of excessive entry; subdividing the generators into five firms would produce better results. Copyright 1992 by University of Chicago Press.